2013
DOI: 10.1108/jmd-02-2012-0034
|View full text |Cite
|
Sign up to set email alerts
|

Social climate as a mediator between leadership behavior and employee well-being in a cross-cultural perspective

Abstract: Citation: Muhonen, T., Jönsson, S., Denti, L., & Chen, K. (2013). Social climate as a mediator between leadership behavior and employee well-being in a crosscultural perspective. Journal of Management Development, 32(10), 1040-1055. AbstractPurpose -The purpose of this paper is to examine the direct effects of empowering and employee-centered leadership on well-being, and the indirect or mediating role of social organizational climate between leadership behavior and well-being in a cross-cultural perspective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…Because heterogeneity, I 2 , is a function of the random effects t 2 and the sampling variance s 2 , I 2 = t 2 / ( s 2 + t 2 ) (Higgins & Thompson, ), the large heterogeneity observed in this review means that the between‐study variance is substantially larger than the total within‐study variance. The relatively large differences among observed correlations are likely to depend on the measurement instruments, the cultural setting (e.g., Kara, Uysal, Sirgy, & Lee, ; Muhonen, Jönsson, Denti, & Chen, ; cf . forest plots in the Supporting Information), and some degree of misclassification of predictor and outcome constructs, rather than on the study characteristics considered in the sensitivity analysis reported in the Results section.…”
Section: Discussionmentioning
confidence: 99%
“…Because heterogeneity, I 2 , is a function of the random effects t 2 and the sampling variance s 2 , I 2 = t 2 / ( s 2 + t 2 ) (Higgins & Thompson, ), the large heterogeneity observed in this review means that the between‐study variance is substantially larger than the total within‐study variance. The relatively large differences among observed correlations are likely to depend on the measurement instruments, the cultural setting (e.g., Kara, Uysal, Sirgy, & Lee, ; Muhonen, Jönsson, Denti, & Chen, ; cf . forest plots in the Supporting Information), and some degree of misclassification of predictor and outcome constructs, rather than on the study characteristics considered in the sensitivity analysis reported in the Results section.…”
Section: Discussionmentioning
confidence: 99%
“…Citation r Organizational citizenship behaviors 3 Auh, Menguc, and Jung (2014) .14** (GL) .37** (IL) Raub and Robert (2010) .28* Humborstad et al (2014) .44* Performance 3 Harris et al (2014) .30** Humborstad et al (2014) .38* Vecchio et al (2010) .33** Psychological empowerment 5 Auh et al (2014) .21** (GL) .47** (IL) Chen et al (2011) .45* (S1) .27* (S2) Konczak et al (2000) .46* Raub and Robert (2013) .46* Raub and Robert (2010) . -Córcoles et al (2013) .32** Self determination 1 Yagil and Gal (2002) .31** Service climate 1 Yagil and Gal (2002) .35** Shared values 1 Clark, Hartline, and Jones (2009) .12* Skills 1 Yagil and Gal (2002) .21** Social climate 1 Muhonen, Jonsson, Denti, and Chen (2013) .56** Teamwork behaviors 1 Chen et al (2011) .21* (S1) .15* (S2) Trust in leader 1 Bobbio, Bellan, and Mangenelli (2012) .76** Turnover intentions 1 Chen et al (2011) −.29* (S1) −.25* (S2) Voice 1 Raub and Robert (2013) .26* Note. For individual-level constructs, empowering leadership was measured at the team or individual level in studies listed.…”
Section: Constructmentioning
confidence: 99%
“…In addition, the traditional research field of employee well-being and leadership has mostly utilized psychometric approaches (e.g., Donaldson-Feilder et al 2013;Kelloway et al 2012a;Muhonen et al 2013). These approaches operate in the form of testing settings, mediator/moderator frameworks, and/or fixed questionnaires with Likert scales to reveal the association between leadership and employee well-being, which are thus treated as predetermined phenomena.…”
Section: Theoretical Backgroundmentioning
confidence: 99%